Review on the Expert Systems for Airport Pavements Maintenance Management - Nooruldeen Mohammed Kareem, Asma Thamir Ibraheem (Mathematical Statistician and Engineering Applications, 2022)
Airport networks are one of a country's most valuable assets, especially as air travel has become more prevalent as a form of transportation. To maintain the maintenance and rehabilitation program, the aviation agency must make significant time and financial commitments. For the proper functioning of airports and to keep the pavements in good shape, airport pavements need to be continuously improved, repaired, and maintained.